Peoples' tribunals and international law / edited by Andrew Byrnes, University of New South Wales, Sydney and Gabrielle Simm, University of Technology Sydney. - Byrnes, Andrew; Simm, Gabrielle (Cambridge University Press, 2018)
Peoples' Tribunals and International Law is the first book to analyse how civil society tribunals implement and develop international law. With contributions covering tribunals in Europe, Latin America and Asia, this edited collection provides cross-disciplinary academic and activist perspectives and unique insights into the phenomenon of peoples' tribunals. Written by academics in law, anthropology and international relations, it also incorporates the reflections of civil society activists and advocates on peoples' tribunals. The collection includes chapters ranging from the Permanent Peoples' Tribunal, successor to the Bertrand Russell Tribunal established to question the legality of the Vietnam War, to recent tribunals addressing atrocities in Soeharto's Indonesia and violations against migrants in Europe. Peoples' Tribunals and International Law offers the first sustained analysis of the different approaches to international law in tribunal proceedings. It will interest scholars of law, criminology, human rights, politics, sociology, anthropology and international relations.